Evaluation of factors leading to poor outcomes for pediatric acute lymphoblastic leukemia in Mexico: a multi-institutional report of 2,116 patients - Moreira, Daniel C.; González-Ramella, Oscar; Echavarría Valenzuela, Maite; Carrillo, Angela K.; Faughnan, Lane; Job, Godwin; Chen, Yichen; Villegas, Cesar; Ellis Irigoyen, Andrea; Barra Urbays, Rosario; Ramírez Martinez, Maribel; Altamirano Alvarez, Eduardo; et al. (Frontiers in Oncology, 2023)
Background and aims: Pediatric acute lymphoblastic leukemia (ALL) survival rates in low-and middle-income countries are lower due to deficiencies in multilevel factors, including access to timely diagnosis, risk-stratified therapy, and comprehensive supportive care. This retrospective study aimed to analyze outcomes for pediatric ALL at 16 centers in Mexico.Methods: Patients <18 years-of-age with newly diagnosed B-and T-cell ALL treated between January 2011 and December 2019 were included. Clinical and biological characteristics and their association with outcomes were examined.Results: Overall, 2,116 patients with a median age of 6.3 years were included. B-cell immunophenotype was identified in 1,889 (89.3%) patients. Median white blood cells at diagnosis was 11.2.5x10 3 /mm 3 . CNS1 status was reported in 1,810 (85.5%), CNS2 in 67 (3.2%), and CNS3 in 61 (2.9%). 1,488 patients (70.4%) were classified as high-risk at diagnosis. However, in 52.5% (991/1,889) of patients with B-cell ALL, the reported risk group did not match the calculated risk group allocation, based on NCI criteria. FISH and PCR tests were performed for 407 (19.2%) and 736 (34.8%) patients. Minimal residual disease (MRD) during induction was performed in 1,158 patients (54.7%). Median follow up was 3.7 years. During induction, 191 patients died (9.1%) and 45 patients (2.1%) experienced induction failure. A total of 365 deaths (17.3%) occurred, including 174 deaths after remission. Six percent (176) of patients abandoned treatment. The 5-year event-free survival (EFS) was 58.9 ±1.7% for B-cell ALL and 47.4 ±5.9% for T-cell ALL, while the 5-year overall survival (OS) was 67.5 ±1.6% for B-cell ALL and 54.3±0.6% for T-cell ALL. The five-year cumulative incidence of CNS relapse was 5.5±0.6%. For the whole cohort, significantly higher outcomes were seen for patients aged 1-10 years, DNA index >0.9, hyperdiploid ALL, and patients without substantial treatment modifications. In multivariable analyses, age and Day 15 MRD continued to have a significant effect on EFS.Outcomes in this multi-institutional cohort describe poor outcomes, influenced by incomplete and inconsistent risk stratification, early toxic death, high on-treatment mortality, and high CNS relapse rate. Adopting comprehensive risk-stratification strategies, evidence-informed deintensification for favorable-risk patients, and optimized supportive care could improve outcomes.